Estimation of sunflower oil distillation cuts as perspective raw material for obtaining tocoferol and phytosterol concentrates - E. O. Gerasimenko; E. A. Butina; I. A. Dubrovskaya; I. A. Bugayets; O. S. Vorontsova (Новые технологии, 2017)
The analysis of quantitative and qualitative composition of phytosterols and tocopherols in samples of distillation cuts of sunflower oils obtained as secondary products of physical refining has been carried out. It has been found that the tocopherols and phytosterols contained in distillation cuts of sunflower oils corresponded to their analogues that are contained in the feedstock. The levels of tocopherols and phytosterols correspond to the data presented in the foreign literature and allow us to consider domestic distillation cuts as a promising raw material for the production of phytosterols and tocopherol concentrates.